Inflation, Taxation and Capital Cost - Villy Bergström; Jan Södersten (The Research Institute of Industrial Economics (IUI), 1979)
In times of inflation, most existing systems of taxation introduce new distortions into the allocation of resources. In this paper, the effects of inflation via taxes on the firm's east of capital are analyzed. The taxes considered are the corporate income tax and household taxes on dividends and capital gains. The first part of the paper presents the model of a firm aiming at maximizing the value of its shares in the portfolios of the stockholders. The nominal east of capital of this firm, financed by equity and debt in a given proportion, is derived. The east of equity and debt are then taken at their nominal values as the firm observes them on the capital market. We then analyze the net real cost of capital, where market rates of return are adjusted for inflation. This makes it possible to determine the net effects of inflation on capital cost, recognizing several counteracting tendencies operating through the tax system. It turns out that for most reasonable assumptions, the real cost of capital will fall as a result of inflation when both profit tax and taxes on dividends and capital gains are taken into account. In the last section finally, we present different ways of indexing the system of taxation to insulate it from inflationary distortions.
Keywords: E31; H21; O16; 330; Inflation; Taxation; Stock